Imam at-Turmudzi's Methodology in Jarh Wa Ta'dil: A Study in Hadith Science - Muhammad Jamil; Dadah, Dadah (al-Afkar, Journal For Islamic Studies, 2025)
This research aims to explore the methods employed by Imam at-Turmudzi in the practice of jarh wa tadil, a critical aspect of Islamic hadith studies focusing on evaluating the reliability of narrators and the authenticity of hadiths. Through a thorough analysis of Imam at-Turmudzi's approach, the study endeavors to understand how his unique methodology contributes to the development of hadith studies and the practice of jarh wa tadil. In a broader context, the research also highlights the importance of jarh wa tadil in ensuring the integrity and authenticity of Islamic teachings, as well as showcasing the diversity of methodologies within the tradition of hadith studies. The research not only provides insights into the contributions of Imam at-Turmudzi but also emphasizes the significance of understanding the methodology of hadith studies to enrich contemporary Islamic discourse.